Capsaicin in Pain Management A Spicy Solution to Chronic and Neuropathic Pain - Konrad Pilarski; Adam Kucharski; Rafał Makuch; Alicja Chrościcka; Kamil Gała; Andrzej Czajka; Paweł Lenard; Sara Michalska; Martyna Dewicka; Alicja Maria Wawrzyniak (Nicolaus Copernicus University in Toruń, 2024)
Introduction and purpose: Chronic pain, defined as pain persisting for three months or longer and neuropathic pain which is a type that arises as a result of damage or disease to the somatosensory system, including peripheral fibers (Aβ, Aδ, and C fibers) and central neurons, are serious conditions pose significant challenges for modern medicine. Addressing these challenges often necessitates a multimodal approach to analgesia, involving the use of multiple analgesic agents with different mechanisms of action. Among these agents is capsaicin, a naturally occurring compound found in hot peppers. This study will collect and analyze information about the applications of capsaicin in pain management, its mechanisms of action, efficacy, and safety Brief description of the state of knowledge: Capsaicin is a natural compound found in chili peppers. This alkaloid is a highly selective agonist of the TRPV1 vanilloid receptor. Upon activation of these receptors, skin nociceptors become less sensitive to stimuli. Incorporating capsaicin into standard chronic and neuropathic pain management may enhance, expedite, and streamline the complex process of treatment, ultimately contributing to improved quality of life for patients and communities. It also offers certain benefits in the treatment of obesity, cardiovascular and gastrointestinal pathologies, various types of cancers, neurogenic bladder, and some dermatological conditions. Materials and Methods: Review and summary of research studies available in databases on Google Scholar and PubMed. Summary: Topically applied capsaicin, especially in the form of an 8% patch is a valuable option for treating peripheral chronic and neuropathic pain, including bone and joint pain. The highest quality evidence has been presented in postherpetic neuralgia and HIV-related pain, where treatment efficacy is comparable to standard treatment.